2011
DOI: 10.1128/aac.01744-10
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of MP-376 (Levofloxacin Inhalation Solution) in Cystic Fibrosis Subjects

Abstract: The pharmacokinetics and tolerability of nebulized MP-376 (levofloxacin inhalation solution [Aeroquin]) were determined in cystic fibrosis (CF) subjects. Ten CF subjects received single 180-mg doses of two formulations of MP-376, followed by a multiple-dose phase of 240 mg once daily for 7 days. Serum and expectorated-sputum samples were assayed for levofloxacin content. Safety was evaluated following the single-and multiple-dose study phases. Nebulized MP-376 produced high concentrations of levofloxacin in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 10 publications
0
47
0
Order By: Relevance
“…Both the uniqueness of mechanistic class and recognized utility of fluoroquinolones in treating CF airway infection make them an attractive candidate for inhaled CF therapy. APT-1026 (levofloxacin inhalation solution, LIS; also formerly known as MP-376) 13 is a formulation of a fluoroquinolone intended for inhaled use in chronic maintenance therapy. We describe the results of a placebo-controlled study designed to evaluate the efficacy and safety of LIS in individuals with CF and chronic P. aeruginosa infection who had previously used inhaled tobramycin.…”
Section: Introductionmentioning
confidence: 99%
“…Both the uniqueness of mechanistic class and recognized utility of fluoroquinolones in treating CF airway infection make them an attractive candidate for inhaled CF therapy. APT-1026 (levofloxacin inhalation solution, LIS; also formerly known as MP-376) 13 is a formulation of a fluoroquinolone intended for inhaled use in chronic maintenance therapy. We describe the results of a placebo-controlled study designed to evaluate the efficacy and safety of LIS in individuals with CF and chronic P. aeruginosa infection who had previously used inhaled tobramycin.…”
Section: Introductionmentioning
confidence: 99%
“…Ciprofloxacin sputum and ELF (151)(152)(153)(154)(155)(156). However, its sputum concentrations measured following aerosolized administration surpass lung tissue or ELF concentrations achieved following oral or intravenous administration by 100-to 1,000-fold, reaching sputum concentrations of almost 3,000 mg/liter (157).…”
Section: Serum and Sputum Pharmacokineticsmentioning
confidence: 99%
“…Observations of CF subjects receiving nebulized formulations of MP-376 (levofloxacin inhalation solution; Aeroquin) at a dose of 180 mg followed by 7 days of daily treatment doses of 240 mg demonstrated high sputum and low serum levofloxacin concentrations. Patients tolerated the MP-376 formulations well, with no serious adverse events reported and no patients excluded during the study due to an adverse event (121). Clinical trials using MP-376 are needed to assess the efficacy and tolerance of this antibiotic in CF subjects with S. maltophilia infections.…”
Section: New Treatment Strategiesmentioning
confidence: 99%
“…That study suggested the potential for the use of levofloxacin as an aerosolized antibiotic in CF patient infections. An additional attractive feature of levofloxacin is the higher maximum concentration of the drug (C max )/MIC and area under the curve (AUC)/MIC values obtained through aerosolized delivery, in contrast to those values obtained for intravenous or oral delivery (121). Observations of CF subjects receiving nebulized formulations of MP-376 (levofloxacin inhalation solution; Aeroquin) at a dose of 180 mg followed by 7 days of daily treatment doses of 240 mg demonstrated high sputum and low serum levofloxacin concentrations.…”
Section: New Treatment Strategiesmentioning
confidence: 99%